2008
DOI: 10.1242/jeb.016683
|View full text |Cite
|
Sign up to set email alerts
|

Honeybees can recognise images of complex natural scenes for use as potential landmarks

Abstract: SUMMARYThe ability to navigate long distances to find rewarding flowers and return home is a key factor in the survival of honeybees (Apis mellifera). To reliably perform this task, bees combine both odometric and landmark cues, which potentially creates a dilemma since environments rich in odometric cues might be poor in salient landmark cues, and vice versa. In the present study, honeybees were provided with differential conditioning to images of complex natural scenes, in order to determine if they could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 59 publications
1
56
0
Order By: Relevance
“…Signal detection theory (Green and Swets, 1966) provides a framework for understanding decision making in situations where perceptual or environmental noise makes discrimination between two signals difficult (Dyer et al, 2008;Wiley, 2006). For example, Fig.1 illustrates a hypothetical signal detection problem faced by bees: flower types that differ in reward value on average differ along some perceptual dimension (such as color), but individual flowers vary in their traits.…”
Section: Uncertainty Signal Detection Theory and Learned Biasesmentioning
confidence: 99%
“…Signal detection theory (Green and Swets, 1966) provides a framework for understanding decision making in situations where perceptual or environmental noise makes discrimination between two signals difficult (Dyer et al, 2008;Wiley, 2006). For example, Fig.1 illustrates a hypothetical signal detection problem faced by bees: flower types that differ in reward value on average differ along some perceptual dimension (such as color), but individual flowers vary in their traits.…”
Section: Uncertainty Signal Detection Theory and Learned Biasesmentioning
confidence: 99%
“…Using this protocol, it has been shown that bees are capable of higher-order forms of visual learning [12,14,21]: they categorize both artificial patterns [31][32][33][34][35] and pictures of natural scenes [36] (see reference [37] for a review), they navigate complex mazes [38,39], exhibit top-down modulation of their visual perception [40], or use spatial configuration to recognize complex pictures [31,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a foraging honeybee may leave a hive and (i) fly several hundred metres through a treed landscape using odometric and landscape cues to judge the distance to a patch containing rewarding flowers (Dyer et al, 2008a;Srinivasan et al, 2000;Vladusich et al, 2005), (ii) at the flower patch detect potential target flowers at a distance and recognise rewarding flowers at 'close' range against background noise using spatial (Dafni et al, 1997), achromatic (Hempel de Ibarra and Vorobyev, 2009) and colour cues (Chittka and Wells, 2004;Dyer et al, 2008b;Giurfa et al, 1996;Hempel de Ibarra and Vorobyev, 2009), and (iii) finally, fly back to the hive and recognise the precise location using a variety of orientation and landmark cues (Dyer et al, 2008a;Srinivasan, 2011;Vladusich et al, 2005). These different tasks are likely to place very different demands upon a visual system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the capacity for humans to read (Ahissar et al, 2009), recognise faces (Collishaw and Hole, 2000;Maurer et al, 2002) or even identify fingerprints (Busey and Vanderkolk, 2005) and abstract 'Greeble' figures (Gauthier and Tarr, 1997) is dependent upon the level of experience with a particular class of stimuli. Whilst it has been assumed that comparatively simple insect brains only allow for vision that is mediated by 'hard-wired' physiological mechanisms (Backhaus et al, 1987;Horridge, 2000;Horridge, 2009a;Horridge, 2009b), several recent studies have shown that what a honeybee perceives is very dependent upon the type of visual experience that an individual animal receives (Avarguès-Weber et al, 2011;Dyer et al, 2008a;Giurfa et al, 1999;Stach et al, 2004;Stach and Giurfa, 2005), and comparative studies of cognitive capacity are of high value . For example, considering pattern vision, the level of discrimination by an individual animal is very dependent upon whether a target stimulus is learned in isolation, which is termed absolute conditioning, or whether a target stimulus is learned in relation to a perceptually similar distractor, which is termed differential conditioning (Giurfa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation